Helix Light Vortex Theory - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
Derivation of the King Plot Anomaly Parameters from First Principles of the Helix Light Vortex Theory (HLV)
Derivation of the King Plot Anomaly Parameters from First Principles of the Helix Light Vortex Theory (HLV)